Relación entre los factores socioeconómicos y la tributación en el departamento de Ucayali en el periodo 2023 - Flores Pezo, Angel Raul (2025)
This study examines the relationship between socioeconomic factors and taxation in the Ucayali region during 2023. Using a quantitative approach, with a correlational level and non-experimental design, data on income, education, consumption expenditure, and monetary poverty were collected and analyzed through statistical regression tools. The results indicate that income levels and education have a positive and significant relationship with taxation, while monetary poverty shows a negative impact. Consumption expenditure, although significant, has a weak influence compared to other variables. With an 2 of 0.8876, the model explains a high proportion of variability in taxation, validating the hypotheses proposed. These findings align with previous studies that emphasize the importance of socioeconomic factors in tax collection. It is concluded that strengthening income levels, improving education, and reducing poverty are key strategies for optimizing taxation in Ucayali. This research provides valuable insights for the design of public policies aimed at improving the equity and efficiency of the tax system in contexts of high economic inequality.